2006
DOI: 10.1118/1.2184437
|View full text |Cite
|
Sign up to set email alerts
|

Computation of relative dose distribution and effective transmission around a shielded vaginal cylinder with Ir192 HDR source using MCNP4B

Abstract: The present work is primarily focused on the estimation of relative dose distribution and effective transmission around a shielded vaginal cylinder with an 192Ir source using the Monte Carlo technique. The MCNP4B code was used to evaluate the dose distribution around a tungsten shielded vaginal cylinder as a function of thickness and angular shielding. The dose distribution and effective transmission of 192Ir by 0.8 cm thickness tungsten were also compared with that for gold and lead. Dose distributions were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…10,16,17 With the current high dose rate (HDR) radiation sources (e.g., 192 Ir), OAR sparing is limited with conventional applicators as the dose distributions are always (quasi-)isotropic around the source. Moreover, even with an intent to deliberately create an anisotropic dose distribution through partial shielding (e.g., a single-channel shielded vaginal applicator with fixed collimation angles of 90°, 180°, or 270°1 6,18 ), such large angles may not be optimal per an early theoretical study on intensity-modulated brachytherapy (IMBT) conducted by Ebert 19 who suggested that optimal plans are generated with collimation angles in the range of 22.5°-45°. The integrated tungsten alloy shields positioned at the two ends of an ovoid applicator can reduce the radiation dose to the bladder and rectum.…”
Section: Introductionmentioning
confidence: 99%
“…10,16,17 With the current high dose rate (HDR) radiation sources (e.g., 192 Ir), OAR sparing is limited with conventional applicators as the dose distributions are always (quasi-)isotropic around the source. Moreover, even with an intent to deliberately create an anisotropic dose distribution through partial shielding (e.g., a single-channel shielded vaginal applicator with fixed collimation angles of 90°, 180°, or 270°1 6,18 ), such large angles may not be optimal per an early theoretical study on intensity-modulated brachytherapy (IMBT) conducted by Ebert 19 who suggested that optimal plans are generated with collimation angles in the range of 22.5°-45°. The integrated tungsten alloy shields positioned at the two ends of an ovoid applicator can reduce the radiation dose to the bladder and rectum.…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified limitations of the current protocol for clinical practice. Others have looked at dose comparison in clinical geometries such as a shielded vaginal cylinder 51,57 or shielded rectal applicator. 56 In these cases, the dose differences were dramatic.…”
Section: Iva Introductionmentioning
confidence: 99%
“…In *F5 tally, the radius of the sphere of exclusion of 1/8 to 1/2 mean free paths (a fixed value of 0.1 cm was used as exclusion distance) was maintained for particles of average energy at the sphere. ( 36 ) The air kerma was estimated from the computed photon energy fluence at a distance of 1 m from the source using the mass energy absorption coefficient (0.0293cm2/g). It may be noted that the energy fluence computed by the *F5 tally of MCNP includes the effect of attenuation and scattering from the source matrix and all surrounding media.…”
Section: Methodsmentioning
confidence: 99%